Gasless laparoscopy as an alternative surgery procedure for postmenopausal women with comorbid diseases - Pawłowicz, Paweł; Uchman-Musielak, Małgorzata; Jakiel, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2012)
Numerous postmenopausal women are in a group with pathologies of female reproductive organs demanding operative treatment. Postmenopausal women are also at an increased risk of a number of health conditions. A review of the literature demonstrated that the laparoscopic procedure using the gasless technique should be recommended to all women with cardiopulmonary risks or with contraindications for general anesthesia.